Expression of antisense or sense RNA of an ankyrin repeat-containing gene blocks chloroplast differentiation in arabidopsis. - Zhang, H (1992)
The Arabidopsis AKR gene that encodes a protein with four ankyrin repeats (a 33-amino acid motif that appears in the 89K domain of the human protein ankyrin) was isolated and characterized. A short sequence outside the ankyrin repeats is similar to that of the protein of the Drosophila muscle segment homeobox (msh) gene. The expression of the AKR gene is light dependent, and transgenic Arabidopsis plants with two or more copies of an antisense or sense AKR construct became chlorotic in a developmentally regulated manner. The chlorotic phenotype was genetically transmitted to the next generation, although most chlorotic plants produced much less seed. Reduced presence of thylakoid membranes and loss of grana are found in the plastids of chlorotic leaves, indicating that antisense or sense AKR has blocked chloroplast differentiation. This study indicates the importance of ankyrin repeat-containing proteins, not only in yeast and animals, but in plants as well.